Precision land leveling for sustainable rice production: case studies in Cambodia, Thailand, Philippines, Vietnam, and India - Nguyen-Van-Hung; Balingbing, Carlito; Sandro, Joseph; Khandai, Suryakanta; Chea, Hong; Songmethakrit, Thanach; Meas, Pyseth; Hitzler, Gerald; Zwick, Walter; Viriyangkura, Ladda; Bautista, Elmer; Gummert, Martin (Springer, 2022)
Laser-controlled land leveling (LLL) can help improve rice production's spatial and temporal management, leading to optimized water and crop management. This research resulted in sustainable performance indicators to illustrate that LLL is a sustainable technology for rice production. The assessment was conducted in Cambodia, the Philippines, Thailand, Vietnam, and India. Benefits of LLL include saving land use, water, and agronomic inputs, increasing yield, and decreasing postharvest losses resulting in saving energy of 3.0–6.9 GJ ha−1and decreasing emissions by 1151–1486 kg CO2-eq ha−1. Additionally, LLL application can obtain a net profit of USD 52–84 ha−1per rice production season in the countries studied. The result demonstrated that LLL is a sustainable technology as well as strongly supports sustainable rice production. The study would lead to better adoption of this technology through its evidence-based promotion.